Clinical Features and Laboratory Analysis of Acute Lymphoblastic Leukemia: The Most Common Type of Leukemia Diagnosed at a Tertiary Care Hospital - KALIMUDDIN MALIK, NIGHAT NASIM (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study was to analyze the most common type of leukemia in the indoor and outdoor patients at Lahore General Hospital/Post Graduate Medical Institute (LGH/PGMI) Lahore. Study Design: A cross-sectional prospective observational study. Setting: Bone Marrow Clinic at LGH and PGMI, Lahore. Duration: A four year study carried out from November, 2008 till November, 2012. Patients and Methods: All cases of Acute Lymphoblastic Leukemia (ALL) diagnosed on bone marrow examination, belonging to all age groups and both sexes were included. The already diagnosed leukemia patients and patients on chemo or radiotherapy were excluded. A detailed relevant history was obtained; general and physical examination, complete blood counts and bone marrow examination were performed. Results: Out of 75 cases diagnosed to have leukemia, acute lymphoblastic leukemia (ALL) was the most common type of leukemia (44%). AML (34.7%) was the second most common type, CML (14.7%) was the third and CLL (4%) was the fourth in order of frequency. There was a single case each of HCL (1.3%) and CMML (1.3%) (Table 1). In the 33 diagnosed patients of ALL, 60% were males and 40% females. ALL cases had a higher rate of frequency in children (55%) as compared to adults (45%). ALL-L2 was the most common subtype of ALL. The most common presenting symptoms were pallor (94%), fever (84%) and weakness (55%). Splenomegaly (79%), hepatomegaly (67%), lymphadenopathy (58%) anemia (94%) thrombocytopenia (72%) and leukocytosis (45%) were important clinical signs. One patient had the congenital anomaly Down’s syndrome. Conclusion: Acute lymphoblastic leukemia ALL is the most common hematological malignancy. It is more frequent in children and male patients. ALL-L2 is the most common subtype noted.